Development of An Android-Based Guidance And Counseling Service Evaluation Instrument For Senior High School - Jannah, Raodatul; Umar, Nur Fadhilah; Saman, Abdul (ILIN Institute Makassar, 2024)
The aim of this study was to determine the needs of Android-based guidance and counseling service evaluation instruments at Man 2 Makassar City, designing Android-based guidance and counseling service evaluation instruments at Man 2 Makassar City. The method used is research and development (R&D) with the ADDIE development model. Data collection was carried out using a Likert scale questionnaire. The results of this study indicate that an evaluation instrument is needed, and there is a need for a special instrument that can be used practically and efficiently. This instrument was developed in the form of an Android application with active menus for activities, progress, and home. The expert assessment of Content Expert 1 obtained a percentage of 77.6% (quite valid). Content Expert 2 obtained a percentage of 78.9% (quite valid). According to the media expert, the result is 86.11% which is included in the criteria very valid. Then based on the overall counselor guidance teacher assessment, this instrument obtained a score of 78.7% which means it is practical to use. In addition, the student assessment resulted in a score of 76.4% which indicates practicality to use.